(untitled) (Nepal Journal of Environmental Science, 2023)
The monsoon season in Nepal brings calamitous events like riverbank erosion, toe cutting, and the structural failure of bridges due to floods. In July 2021, a motorable bridge in Bhadgaun, Tanahun district, Nepal, collapsed during a massive flood in Chhabdi Khola. The study aims to comprehensively document the aftermath, specifically focusing on the causal factors that led to the damage of the Chhabdi Khola Dovan Bridge. The study delves into an in-depth analysis of the stream’s channel morphology, with the 5.85 kilometers Chhabdi Khola partitioned into 28 distinct segments, each spanning approximately 200 meters. These segments, sequentially labeled from Site 1 to Site 28, encompass the area extending from the upstream at Chhabdi Barah temple to the downstream at bridge’s location. Rigorous measurements of length, breadth, and depth at each site form the basis for volumetric assessments of the stream. The study revolves around contrasting paleo channel attributes with contemporary alterations within the Chhabdi Khola catchment. The analysis leverages precipitation data sourced from the Department of Hydrology and Meteorology (DHM) to discern precipitation trends within the Chhabdi Khola catchment area. The hydrographic data underwent trend analysis utilizing Mann-Kendall and Sen’s slope method through R software (version 4.3.2). The collapse of the Chhabdi Khola Dovan Bridge resulted from intense water flow and debris due to heavy rainfall and a narrow outlet near the bridge, impacting the local population and land users facing the enduring aftermath of a catastrophic monsoon event. The study highlights the significance of understanding river dynamics in small streams and advocates for proactive disaster preparedness measures, even in seemingly small river channels.